STUDIES ON THE PREVALENCE, INTENSITY AND IMPACT OF SOME WATER QUALITY PARAMETERS ON PARASITES OF Coptodon zilli - OMEJI, S.; OBANDE, R.A.; KWAGHVIHI, O.B. (Nigerian Journal of Fisheries, 2023)
160 samples of live Coptodon zilli (Redbelly tilapia) were bought from the earthen pond of a reputable fish farm in Makurdi, Benue State, Nigeria. The fish samples were taken to the Biological Science Laboratory for parasitological studies using standard parasitological methods while the physico-chemical parameters of the pond water were assessed in situ and ex situ, following standard procedures. Of the 160 samples, 91 samples were infested with a total prevalence of 56.88% and mean intensity of 63.98. 7 parasite species comprising of Clinostomum sp, Neascus sp, Ichthyophthirius sp, Dactylogyrus sp, Eustrongylides sp, Capillaria sp and Piscicola sp. were recovered from the infested fish samples. Of these parasites, Clinostomum sp had the highest parasitic prevalence of 20.01% (2.50 from the eye socket, 5.00% gill, 5.63% opercula, and 6.88% skin) and mean intensity of 25.94% with the eye socket, gill, opercula, and skin accounting for 4.50, 5.75, 6.78 and 8.91, respectively. Among the infested organs, while the gills had the highest parasitic prevalence of 17.51%, the least parasitic prevalence of 5.63% was recorded for the opercula. Additionally, while the highest mean intensity of 19.97 was recorded for intestinal wall/gut, the least mean intensity of 6.78 was recorded for the opercula. Mean Ammonia free nitrogen (0.73±0.03) and Dissolved oxygen (5.85±0.05) were higher than the recommended limits while the mean pH of 7.45±0.15 and temperature of 25.60±0.30 were within the recommended limits.